2012
DOI: 10.1158/0008-5472.can-12-1223
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Regulation of Epithelial–Mesenchymal Transitions in Cancer

Abstract: The evolution of the cancer cell into a metastatic entity is the major cause of death in cancer patients. Activation of epithelial to mesenchymal transition (EMT) endows invasive and metastatic properties upon cancer cells that favor successful colonization of distal target organs. The observation that in many cancers distant metastases resemble the epithelial phenotype of primary tumors has led to speculation that the disseminated tumor cells recruited to the target organs undergo mesenchymal to epithelial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
245
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(256 citation statements)
references
References 70 publications
5
245
0
6
Order By: Relevance
“…Interestingly, we observe an initial down-regulation of VCAN upon immortalization (FPKM 3 to 0.3) and a subsequent up-regulation in the metastasizing cells (FPKM 1.4 to 5.4). It has previously been shown that VCAN can promote metastatic processes (34), and our results indicate that VCAN may have a dual role, both early and late in tumorigenesis.…”
Section: Validation Of Differentially Expressed Genes On the Protein supporting
confidence: 73%
“…Interestingly, we observe an initial down-regulation of VCAN upon immortalization (FPKM 3 to 0.3) and a subsequent up-regulation in the metastasizing cells (FPKM 1.4 to 5.4). It has previously been shown that VCAN can promote metastatic processes (34), and our results indicate that VCAN may have a dual role, both early and late in tumorigenesis.…”
Section: Validation Of Differentially Expressed Genes On the Protein supporting
confidence: 73%
“…32,37,38,50,51 Our findings that the TLR2 coregulates with TLR6 in MAM led us to the hypothesis that versican may be the relevant TLR2/6 ligand in myeloma BM. However, there are no reports in the literature regarding the role, or even the presence, of versican in the myeloma microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Versican is a large extracellular matrix proteoglycan previously shown to enhance carcinoma metastasis through TLR2/6-mediated nonautonomous activation of myeloid cells in the metastatic niche. [32][33][34][35][36][37][38] However, versican had not previously been implicated in myeloma pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, activation of the EMT is known to endow the invasive and metastatic properties upon cancer cells for the successful colonization of distal target organs (26). Previous studies also revealed that EMT is crucial in drug resistance to EGFR inhibitor in NSCLC (27) and promotes the cell invasion and metastatic property.…”
Section: Discussionmentioning
confidence: 99%